Analysis of the adaptive effect in female athletes at the pre-competition stage of the annual educational and training macrocycle - S. V. Gudimov; A. N. Shkrebko; I. A. Osetrov; V. M. Shaimardanov (National Electronic Information Consortium (NEICON), 2020)
Aim: assessment of the functional state of female students of the sports department of the university involved in track and field athletics at the pre-competition stage of the annual training cycle. Materials and methods. The research was carried out at the Department of Physical Culture and Sports of the Yaroslavl State Medical University. It was attended by 14 students from the athletics section (experimental group) and 20 students not involved in sports sections (control group). Conclusions. The analysis of the obtained data revealed practically equal anthropometric indicators in the experimental and control groups of the examined female students. During the mathematical processing of the results of functional tests, statistically significant differences were established between the indicators of the experimental and control groups of girl students. The Harvard Step test in the athletics group exceeded this indicator in the control group by 21 %. Also, in athletes, a significantly longer (by 23 %) breath holding time was found. A significantly shorter recovery time of the heart rate of female athletes after 20 squats was established, in comparison with untrained ones. The reaction to orthostasis among the athletes was satisfactory, and among the students from the control group it approached unsatisfactory. Results. The results obtained indicate a high level of physical performance and recovery processes of female athletes at the pre-competition stage of the annual training cycle. The best functional state of the cardiovascular, respiratory and vegetative-vascular nervous systems of female athletes was established in comparison with the indicators of female students who do not go in for sports.